O discurso do professor sobre inclusão - Ralin, Vera Lúcia de Oliveira (2013)
This paper examines the meanings assigned by teachers in a public school in São Paulo about school inclusion. Everything these teachers had said was analyzed under the aegis of French Trend of Discourse Analysis. Discussed in this paper, the entanglement between speech therapist and education, laws and concepts of inclusion. An overview of the theory of discourse analysis was drawn to make possible the analysis of data leaving these theoretical bases. Data were collected by recording discussions of two discussion groups with teachers about school inclusion. The videos were transcribed and analyzed using as methodology the French Line of Discourse Analysis. Thus, it enables to understand speech in addition to what is said, and to reveal ideological marks of the teacher's discourses about school inclusion. We consider the meanings of school inclusion, assigned by teachers, is set up initially by promoting socialization, by intertwining between speeches, and analyst intervention and analysis of the unsaid. We noticed that the speeches attribute also the sense of providing teaching / learning to the subject with disabilities. We concluded that it needs a (re)signification of the discourse about inclusion, other ideological brands. And for that, it is necessary the school be embraced from the perspective of a collaborative work